2001
DOI: 10.1159/000047858
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Hepatocyte Spheroid Formation for Hepatic Tissue Engineering on Three-Dimensional Biodegradable Polymer within a Flow Bioreactor prior to Implantation

Abstract: We hypothesize that in vitro conditioning of hepatocytes within biodegradable poly-L-lactic acid (PLLA) polymer matrices prior to implantation may increase hepatocyte survival and function after transplantation. The purpose of this study was to optimize the culture conditions of hepatocytes in a pulsatile flow bioreactor. PLLA discs were seeded with rat hepatocytes in a concentration of 2.5, 5, 10, 20 and 40 × 106 cells/ml. Seeded discs were exposed to recirculated perpendicular flow of 0, 7, 15, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 31 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…These spheroid-like structures in the 3D cultures did not exceed a diameter of 150 lm which should allow sufficient sustenance of the inner cells. 20 The cluster area of the highest concentrated cells increased slightly within the first week of cultivation but the following week did not yield further augmentation which is rather likely due to reduced proliferation caused by contact inhibition. 21 A similar behavior was published previously about HepG2 cells grown as an organotypic culture in spheroid-like structures.…”
Section: Discussionmentioning
confidence: 94%
“…These spheroid-like structures in the 3D cultures did not exceed a diameter of 150 lm which should allow sufficient sustenance of the inner cells. 20 The cluster area of the highest concentrated cells increased slightly within the first week of cultivation but the following week did not yield further augmentation which is rather likely due to reduced proliferation caused by contact inhibition. 21 A similar behavior was published previously about HepG2 cells grown as an organotypic culture in spheroid-like structures.…”
Section: Discussionmentioning
confidence: 94%
“…24,25 In the pulsatile flow bioreactor culture, primary rat hepatocytes preserved viability, morphology, and differentiated function as demonstrated by functional and structural analysis. We presume that the formation of spheroids is an advantageous configuration in improving the posttransplantation viability of hepatocytes.…”
Section: Discussionmentioning
confidence: 97%
“…24,26,27 Polymers were manufactured to dimensions of 18 mm diameter and 1 mm thickness, with a pore size of 200 to 400 mm, and then cold-gas sterilized with ethylene oxide (H.W. Anderson Products, Chapel Hill, NC) before use.…”
Section: Polymer Fabricationmentioning
confidence: 99%
“…In a previous study we had found that the optimal flow culture conditions for rat hepatocytes on highly porous PLLA were a seeding concentration of 10 × 10 6 cells/ml with a flow rate of 24 ml/min [58]. The optimal outcome of flow culture was defined by the highest density of spheroids within the polymer and the highest ratio of aggregated versus nonaggregated hepatocytes.…”
Section: Discussionmentioning
confidence: 99%